Double-heterojunction photodetector for midinfrared applications: Theoretical model and experimental results - Chakrabarti P.; Krier A.; Morgan A.F. (My University, 2025)
We report a theoretical model for characterization of a double heterojunction (DH) photovoltaic detector for application in the midinfrared (MIR) wavelength region. The physics-based closed-form model developed here has been applied to study the characteristics of an n+-InAsSbP-n°-InAsSb-p+-InAsSbP DH detector grown by liquid-phase epitaxy (LPE) for possible application in the 2- to 5-μm wavelength region. The results obtained from the experimental measurements have been compared and contrasted with those predicted on the basis of the theoretical model. The model can be used to explain the various physical mechanisms that shape the characteristics of the device under room-temperature operation. It can also be used to optimize the performance of the photodetector to suit specific requirements. The study reveals that compositional grading in the active and the cladding regions of a DH grown by LPE is responsible for the reduction of the responsivity and detectivity of the device in the shorter wavelength region.